IDENTIFIKASI MISKONSEPSI SISWA KELAS XI IPA MAN 2 LAMONGAN MENGGUNAKAN INSTRUMEN TES DIAGNOSTIK FIVE TIER PADA KONSEP LAJU REAKSI - Siti Ririn Lailiyatul Mualifah; Mike Rahayu (Berajah Journal, 2023)
This study aims to determine the misconceptions experienced by students using a five-tier diagnostic test instrument on the concept of reaction rate and to determine the factors that cause misconceptions experienced by students on the concept of reaction rate. This study uses a quantitative descriptive method. The sampling technique used purposive sampling technique. The sample in this study consisted of 30 students of class XI IPA 5 MAN 2 Lamongan for the 2021/2022 academic year. The instrument used in this study was a five-tier diagnostic test consisting of 26 questions. Analysis of the trial data results obtained a reliability coefficient of 0.846 with high criteria. The results showed that students experienced misconceptions about the reaction rate sub-concept of 26.67%, the collision theory sub-concept of 63.34%, the effect of temperature on the reaction rate sub-concept was 57.78%, the catalyst and activation energy sub-concept was 12.21%, the reaction order sub-concept was 18.90%, the sub-concept was preventing physical and chemical changes by 26.66%. Factors that cause students' misconceptions come from preconceptions, low basic abilities of students, students' interest in learning the concept of reaction rate, and student learning resources from the internet.